2014
DOI: 10.1371/journal.ppat.1003976
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Type-I IFN under Lymphopenic Conditions Alters CD4 T Cell Homeostasis

Abstract: HIV infection and the associated chronic immune activation alter T cell homeostasis leading to CD4 T cell depletion and CD8 T cell expansion. The mechanisms behind these outcomes are not totally defined and only partially explained by the direct cytopathic effect of the virus. In this manuscript, we addressed the impact of lymphopenia and chronic exposure to IFN-α on T cell homeostasis. In a lymphopenic murine model, this interaction led to decreased CD4 counts and CD8 T cell expansion in association with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…We have shown that, in the context of lymphopenia, IL-7 drives increased expression of STAT1, enhancing the response to type I IFNs. In addition, in the setting of chronic exposure to type I IFNs, this mechanism led to the preferential depletion of the CD4 effector memory phenotype (37). The present data suggest that HIV alters T cell homeostasis and cytokine responses, leading to the depletion of the CD4 + T cell pool.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We have shown that, in the context of lymphopenia, IL-7 drives increased expression of STAT1, enhancing the response to type I IFNs. In addition, in the setting of chronic exposure to type I IFNs, this mechanism led to the preferential depletion of the CD4 effector memory phenotype (37). The present data suggest that HIV alters T cell homeostasis and cytokine responses, leading to the depletion of the CD4 + T cell pool.…”
Section: Discussionmentioning
confidence: 57%
“…However, several reports have also shown its ability to activate STAT1, although this pathway is not well characterized (34)(35)(36). We found that IL-7 in vitro can modulate the expression levels of STAT1 protein, which we will refer to as total STAT1 protein (t-STAT1), to distinguish it from the activated phosphorylated form, p-STAT1 (37). We hypothesized that upregulation of t-STAT1 may induce changes in the usage of STATs when T cells respond to IL-7.…”
Section: Il-7 Induces Expression and Activation Of Stat1mentioning
confidence: 89%
See 1 more Smart Citation
“…An acute viral infection triggers immediate and potent type I interferon production by a variety of cells, leading to upregulation of hundreds of genes (the “interferon-stimulated genes”) (77). In the context of chronic HIV-1 infection, persistent interferon signaling has been associated with increased CCR5 and PD-1 expression, upregulation of indoleamine 2,3-dioxygenase and other inflammatory pathways, reduced thymopoieses, the generation of dysfunctional T cells and altered T cell homeostasis (7881). Higher levels of interferon signaling are also correlated with poor immune reconstitution (81, 82).…”
Section: Immune Modulating Drugsmentioning
confidence: 99%
“…Although rhesus macaques treated with type I IFNs are more resistant to SIV infection, chronic type I IFN stimulation during infection renders cells refractory to further type I IFN stimulation by inducing negative regulators of type I IFN signaling, which leads to increased virus loads in treated animals compared with placebo controls (196). In a murine model of lymphopenia, chronic type I IFN exposure leads to CD4 + T cell depletion and CD8 + T cell expansion (197). Therefore, these findings suggest that type I IFNs promote CD4 + T cell depletion independently of the effects of HIV and explain how neutralizing IFN-a may delay AIDS disease progression (191).…”
Section: Hivmentioning
confidence: 99%